Low temperature CO oxidation and CH4 combustion over Co3O4 nanosheets. (1st September 2017) - Wang, Fagen; Zhang, Linjia; Xu, Leilei; Deng, Zhiyong; Shi, Weidong
Graphical abstract: Highlights: Nanosheets of Co3 O4 nanomaterials were synthesized in mediates of EG and water. Co3 O4 nanosheets showed higher performance for oxidations of CO and methane. The more active oxygen species in the Co3 O4 nanosheets were contributed to the higher performance. Abstract: Co3 O4 nanomaterials were synthesized by hydrothermal method and were applied for low temperature CO oxidation and methane combustion. The addition of ethylene glycol and its concentration significantly influenced the size and shape of the Co3 O4 oxides. Nanosheets of Co3 O4 were synthesized in ethylene glycol solution and nanospheres were formed in water. The activity of oxygen species in the nanosheets and nanospheres were characterized by hydrogen/methane programmed reduction, oxygen programmed desorption and XPS. The results showed that the Co3 O4 nanosheets exhibited more active oxygen species than the Co3 O4 nanospheres, leading to the higher activity in the oxidative reactions. The study demonstrated the importance of active oxygen species in Co3 O4 catalysts to achieve high catalytic performance towards the carbon monoxide and methane elimination at low temperatures.